Exploring Students' Perceptions Toward Drama Project in Enhancing Their Speaking Ability in English Education Study Program - Azzahra, Farras; Hayati, Rita (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The aims of this research were to explore students’ perceptions toward drama project and identified the specific aspects of speaking that have improved through their participation in drama project. This research was conducted at Sriwijaya University, which involved 10 students of English Education study program who had taken the “Literature in ELT” and involved in drama project as a part of the coursework. This research employed qualitative research methods and the data of this research were collected through semi-structured interview. The findings revealed that most of the students perceived drama project as an effective approach and acknowledged its role in improving their speaking abilities. They expressed significant improvements in pronunciation, intonation, fluency due to frequent practices. The collaborative aspects of drama also contributed to help them enhance their confidence. However, several challenges were also faced by the students, including nervousness, memorizing long dialogues, technical problem, and limited speaking lines for certain participants. In addressing those challenges, they do more practice and sought feedback from their peers and lecturers. This study suggests that educators provide sufficient practice time, ensure equal speaking opportunities for all participants, and provide continuous help and feedback to optimize the benefits of drama-based learning activities. This study offers valuable insights and suggestions for students, educators, and future researchers.